Independent Learning from Home Based on Self-Efficacy - Fitria Kristanti Eka Putri; Eka Putri Azrai; Ade Suryanda (Jurnal Pendidikan Biologi, 2022)
Student learning independence in biology subjects in high school while learning from home is of course very much needed to maintain and improve the quality of learning. One of several factors that influence is self-efficacy. This study aims to determine the correlation of self-efficacy with student learning independence in biology subjects in high school while learning from home and was carried out at SMA Negeri 21 Jakarta in January 2020/2021 academic year. The method used is descriptive quantitative with correlation studies. The sample used was 106 students of class XI MIPA who were selected through simple random sampling technique. Data was collected using a survey technique that used self-efficacy instruments and students' independent learning instruments in biology subjects in high school while learning from home. The results of the analysis show that there is a positive correlation between self-efficacy independent learning in biology subjects in high school while learning from home and both variables are included in the high-level criteria. Self-efficacy is very important because it will give students more strength internally to always feel confident in their abilities. This supports students to be able to follow the biology learning process and be able to complete assignments well. Finally, students can organize all actions to achieve the desired goals while studying from home and achieving the maximum quality of learning biology.